(untitled) (Patan Pragya, 2021)
This paper reflects the situation of foreign labour migration of Nepalese People. Globally, foreign labour migration is in increasing trends. In Nepalese context also foreign labour migration is being more important for employment mainly among unemployed people and youths who entered in labour force market. The number of foreign labour migrants and share of remittance in terms of GDP has increased. This article is based on secondary sources of information. The Global Commission on International Migration (GCIM) describes the driving forces in international migration in terms of “3Ds” (development, demography and democracy). In one side foreign labour migration has contributed to reduce poverty level and in other the income gap among migrants and non-migrants been increased. In addition, due to mail domination in foreign labour migration the role of women has been changed in households and society. It has contributed women empowerment mainly in male labour migrant’s households. Migration has occurred throughout history, and current trends certainly indicate that it will continue to increase in the future. The forces of globalization have created opportunities for greater integration of labour market globally.